Les larmes et le sang des chiites : corps et pratiques rituelles lors des célébrations de ‘Âshûrâ’ (Liban, Syrie) - Sabrina Mervin (Revue des Mondes Musulmans et de la Méditerranée)
The ‘Âshûrâ’ rituals that the Shii observe to commemorate the martyrdom of their third Imam, Ḥusayn, at Kerbela, have gained more visibility these last years. The fact boosts the debates among ulama and believers about the mortification rituals observed by penitents. In order to express the devotion that they dedicate to their imam, the believers perform the tragedy, are in mourning, cry, but also they beat their chest and make they blood flow during public rituals. We describe here these rituals among different Shii groups (in Lebanon and Syria), stressing on the relation that is set between the body and the sacred.